Productivity Growth in Romania A Firm-Level Analysis - Iootty, Mariana (World Bank E-Library Archive, 2019)
This paper examines productivity growth in Romania using balance sheet data for a census of Romanian firms in 2011-17. Three measures of productivity are estimated: labor productivity, revenue total factor productivity, and revenue total factor productivity adjusted for markups. Drawing from these measures, the paper follows a two-step approach to answer two fundamental questions: (i) who are the firms-and what are their key characteristics-driving and dragging productivity growth in Romania? and (ii) what are the drivers behind productivity expansion? A first step of the analysis characterizes productivity leaders and laggards, finding that companies at the domestic productivity frontier are older and larger, have higher capital intensity, and pay higher wages. Domestic market leaders charge higher markups, especially in manufacturing, but are not becoming more efficient. A second step of the analysis decomposes aggregate productivity growth and finds that reallocation of market shares to more efficient players has been the main driver in manufacturing but not in services, which are typically more sheltered from competition. At the same time, individual firms are becoming less productive, suggesting that there is scope to improve firm capabilities, particularly in services. These findings suggest a policy agenda for Romania centered on removing distortions to competition and boosting human capital